Assessment of the intrinsic interactions of nanocomposite polyaniline/SBA-15 with carbon dioxide: Correlation between the hydrophilic character and surface basicity. (July 2018) - Boukoussa, Bouhadjar; Hakiki, Aboubakr; Nunes-Beltrao, Ana Paola; Hamacha, Rachida; Azzouz, Abdelkrim
Graphical abstract: Highlights: In-situ polymerization of various amounts of aniline inside the mesoporous SBA-15 silica. Incorporation of thin layers of polyaniline induces affinity towards carbon dioxide. Chemical interactions between CO2 molecules and the amine-moieties-containing nanocomposites. Physical interactions between the H2 O and the carbon dioxide. Effect of the repetitive adsorption-desorption cycles on CO2 and water sorption. Abstract: This work focuses on the preparation and modification of mesoporous SBA-15 silica by in-situ polymerization of various amounts of aniline. The resulting nanocomposites denoted as pani/SBA-15 displayed affinity towards CO2 . X-ray diffraction, argon sorption isotherms at 87 K, thermogravimetric analysis, Fourier transform infrared spectroscopy and scanning electronic microscopy revealed the formation of thin layers of pani in the inner surface of SBA-15. The surface basicity and hydrophilic character expressed in terms of retention capacity of CO2 (CRC) and moisture (WRC) were assessed through thermal programmed desorption. The CRC was found to increase with increasing polyaniline content. CO2 appears to adsorb via both physical and chemical interactions on three types of sites. The weak sites are due to physical interactions between H2 O and CO2 molecules, while the strong sites are expressed by chemical interactions between CO2 molecules and the amine moiety incorporated. Repetitive TPD patterns showed a progressive CRC decrease due to the removal of water molecules that contribute significantly to CO2 retention.